Về một xấp xỉ ước lượng Bayes trong mô hình thống kê phi tuyến - Quang, Ung Ngọc (Journal of Computer Science and Cybernetics, 2016)
In this note,we consider the problem of finding an approach to the Bayesian estimates in the nonlinear statistical models X=j(q) + e, where X is a matric of observations, j is a known nonlinear function, and qÎQ, Q is a compact subset of R1.